Antioxidant activity-guided isolation of constituents from Euphorbia gaditana Coss. and their antioxidant and tyrosinase inhibitory activities. (October 2020) - Badaoui, Mohamed Ibrahim; Magid, Abdulmagid Alabdul; Voutquenne-Nazabadioko, Laurence; Benkhaled, Mohammed; Harakat, Dominique; Robert, Anthony; Haba, Hamada
Graphical abstract: Highlights: A phytochemical study of Euphorbia gaditana was carried out. Two previous unreported compounds type acetophenone and α-pyrone, along with 29 known compounds were identified. An antioxidant activity-guided isolation was performed using DPPH and CUPRAC assays. All extracts and isolated compounds were evaluated for their antioxidant activity. The tyrosinase inhibitory activity was estimated for the two previous unreported molecules. Abstract: Two previously unreported compounds, 4- O -(2′′- O -galloyl- β -d -glucopyranosyl)-3, 5-dihydroxyacetophenone (1 ) and 5-isopropyl-2-oxo-3, 6-dihydropyran-4-carboxylic acid (2 ), along with twenty-nine known compounds (3−31 ) were isolated from the aerial parts of Euphorbia gaditana Coss. Their structures were elucidated based on extensive spectroscopic analysis 1D and 2D-NMR, mass spectrometry HR-ESI-MS, optical rotation [α]D, acid hydrolysis and the comparison of NMR data with those described in literature. The antioxidant activity-guided study was conducted using DPPH and CUPRAC methods started from the extracts to bioactive isolated molecules. Most of the isolates (1-31 ) showed a good to excellent antioxidant activity compared to the standards BHT and ascorbic acid. Furthermore, 1 and 2 exhibited a moderate tyrosinase inhibitory activity (IC50 89.78 ± 0.93 and 52.39 ± 0.69 μg/mL, respectively) compared to the standard kojic acid (IC50 25.23 ± 0.78 μg/mL).